1994
DOI: 10.1007/bf00283870
|View full text |Cite
|
Sign up to set email alerts
|

Multicopy suppresors, mssA and mssB, of an smbA mutation of Escherichia coli

Abstract: We have isolated and characterized two multicopy suppressors, mssA and mssB, which suppress the cold-sensitive growth phenotype of the smbA2 mutant of Escherichia coli. The mssA gene is located immediately upstream of the rpsA gene (20.5 min). MssA protein was found to be related to nucleoside monophosphate kinases. The mssB gene was found to be identical to the deaD gene (69 min), which encodes a putative RNA helicase. The SmbA protein belongs to the aspartokinase family and probably represents a new, fourth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…The kanamycin-resistant gene (1.3-kb HincII fragment) from pUC7Km(Pst) was inserted into the middle of the coding region of the csdA gene (alternatively, deaD and mssB) at the EcoRV site in pKX164 (65), yielding pKNJ9026. The linearized pKNJ9026 DNA fragment containing the disrupted csdA gene (csdA::kan) was then introduced into the chromosome of a recD mutant FS1576 (recD1009 thi-1 thr-1 leuB6 lacY1 tonA21 supE44).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kanamycin-resistant gene (1.3-kb HincII fragment) from pUC7Km(Pst) was inserted into the middle of the coding region of the csdA gene (alternatively, deaD and mssB) at the EcoRV site in pKX164 (65), yielding pKNJ9026. The linearized pKNJ9026 DNA fragment containing the disrupted csdA gene (csdA::kan) was then introduced into the chromosome of a recD mutant FS1576 (recD1009 thi-1 thr-1 leuB6 lacY1 tonA21 supE44).…”
Section: Methodsmentioning
confidence: 99%
“…5, the pnp mutant was extremely sensitive to low temperature and was unable to form colonies below 25°C, which agrees well with the results reported by Luttinger et al (41); the colony-forming ability dropped to 10 Ϫ7 . The cold-sensitive growth phenotype of the pnp mutant was fully complemented by transforming cells with plasmid pKX150 carrying the pnp ϩ gene (65), indicating that PNPase function is essential for growth at low temperature but not at high temperature.…”
Section: Figmentioning
confidence: 99%
“…For nucleotide pool determinations, the Tris-buffered medium of Edlin and Maaløe (12) with 0.3 mM phosphate was used. Cells were labeled for at least one generation of exponential growth in this medium containing 32 P i with a specific activity of 33 Ci/mol. A 0.5-ml aliquot of the labeled culture was filtered onto a 13-mm membrane filter (0.45-m pore size), and the filter was extracted with 0.2 ml of ice-cold 0.3 M formic acid.…”
Section: Methodsmentioning
confidence: 99%
“…The P25 gene was therefore designated mssA (multicopy suppressor of smbA). The deduced amino acid sequence of mssA indicated that it was related to a nucleoside monophosphate kinase (32).…”
mentioning
confidence: 99%
“…The N-terminal globular domain of MukB binds to filaments of the FtsZ protein polymer (12) and to eukaryotic microtubules in vitro (13). To analyze the in vivo function of MukB, various suppressor mutations and syntheticlethal mutations have been identified (10,(25)(26)(27). Mutations of the topA gene, encoding topoisomerase I, suppress the temperature-sensitive growth and anucleate cell production caused by null mutation of each muk gene.…”
mentioning
confidence: 99%